2013
DOI: 10.1159/000343376
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 and Connexin40 Mediate the Normal Shear Stress-Induced Inhibition of the Proliferation of Endothelial Cells Co-Cultured with Vascular Smooth Muscle Cells

Abstract: Background: Shear stress imposed by blood flow directly impacts endothelial cells (ECs), which are simultaneously influenced by neighboring vascular smooth muscle cells (VSMCs). However, the mechanisms by which shear stress and VSMCs modulate EC proliferation remain to be elucidated. Methods: ECs, cultured alone or co-cultured with VSMCs, were subjected to a normal level of laminar shear stress (NSS) of 15 dyne/cm2 or kept under static conditions by using a parallel-plate flow chamber system, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
0
14
1
Order By: Relevance
“…It should be noted that in the present study, we found that shear stress of 5 dyn/cm 2 decreased the level of Cx40 in HCAECs co-cultured with HCSMCs, while shear stress of 12 dyn/cm 2 had no effect, which is not consistent with the findings in the previous study of HUVECs [38]. This discrepancy may be attributed to the difference in the cell lines used, indirectly supported by the difference of HCAECs and HUVECs in the wound closure under low laminar shear stress (3 dyn/cm 2 ) [39].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It should be noted that in the present study, we found that shear stress of 5 dyn/cm 2 decreased the level of Cx40 in HCAECs co-cultured with HCSMCs, while shear stress of 12 dyn/cm 2 had no effect, which is not consistent with the findings in the previous study of HUVECs [38]. This discrepancy may be attributed to the difference in the cell lines used, indirectly supported by the difference of HCAECs and HUVECs in the wound closure under low laminar shear stress (3 dyn/cm 2 ) [39].…”
Section: Discussioncontrasting
confidence: 99%
“…In case of Cx40, a previous study showed that its endothelial protein expression was elevated markedly by shear stress from 6-10 dyn/cm 2 , while higher shear stress did not affect the expression of Cx40 in HUVECs cultured alone compared to static conditions [20]. However, an earlier study showed that shear stress of 15 dyn/cm 2 downregulated the level of Cx40 expression in rat aortic HUVECs co-cultured with HUVSMCs compared to static conditions [38]. These discrepancies might be explained by different cellular culture models used in the studies and suggested that SMCs might affect the mechanical response of ECs to shear stress.…”
Section: Discussionmentioning
confidence: 93%
“…SIRT1 has been proved to play critical roles in vascular homeostasis and remodeling [22,39]. Here, using SIRT1 activator-resveratrol, SIRT1 overexpression plasmid, specific siRNA transfection, and knockout mice, we revealed the protective role of SIRT1 in maintaining the normal contractile differentiation of VSMCs.…”
Section: Discussionmentioning
confidence: 90%
“…To further study the role of SIRT1, FOXO3a and FOXO4 in response to mechanical stretch, resveratrol, an activator of SIRT1 [22] was used to stimulate SIRT1 in VSMCs under static conditions. The results showed that VSMCs treated with resveratrol (1 μM) did not have a significant effect on the expression of SIRT1, whereas 10 μM, 25 μM, 50 μM and 100 μM Resveratrol all significantly increased the expression of SIRT1 (Fig.…”
Section: Resveratrol Modulated Expression Of Foxo3a Foxo4 and Contramentioning
confidence: 99%
“…In mice, neointima formation is accompanied by a progressive down-regulation of SIRT1 [19]. In cultured endothelial cells, laminar flow increases whereas oscillating flow decreases the expression and activity of SIRT1 [20, 21]. Despite this information, it is unclear whether or not endothelial SIRT1 modulates arterial remodeling, and if so, by what mechanism(s).…”
Section: Introductionmentioning
confidence: 99%